Knowledge Alignment Workshop: "What Do We Know?" - Bonilla, Melissa; Muller, Anna; Ortiz, Berta; Zapata, Emmanuel; Londoño, Juan Manuel (2025)
Knowledge Alignment Workshop: "What Do We Know?" Scope fase of the design cycle​ Workshop Overview​ Duration: 2.5 - 3 hours ​ Goal: Align team knowledge, identify expertise gaps, and establish shared understanding​ Inspired by the exercise "What do we know?" by IDEO, we created this as a kick off project workshop, to help us to understand the needs of the team/project and analyse how the HCD approach could interact with it. It will help us to better understand and contribute into the teams/projects.